Nerve growth factor as an important possible component of novel therapy for cancer, diabetes and cardiovascular diseases - Steckiewicz, Karol P; BarciÅ„ska, Ewelina; WoÅºniak, MichaÅ‚ (Cellular and Molecular Biology, 2018)
Nerve growth factor (NGF) is protein discovered by Rita Levi Montalcini in the 1950s. It plays a crucial role in the development of nervous system. NGF may be produced by a variety of cells even beyond nervous system. NGF modulate cell metabolism by binding to p75NTR and TrkA receptors. NGF is involved in psychological processes and may be the possible therapeutical agent for diabetes, cancer and cardiovascular diseases, which will be described in the article.